Accountant Behavior and Islamic Ethics as Mediators Among Accounting Service and Decision-Making Quality - Zaki Sima Fashimado; Darmawan Darmawan; Erna Fitri Komariyah (JURNAL AKUNTANSI DAN AUDITING, 2026)
Accounting service quality is widely assumed to improve professional decisions, yet the mechanism transmitting that effect remains unspecified. This study examines Indonesian corporate accountants, a setting where professional standards operate alongside Islamic ethical commitments, and asks whether accountant behaviour and Islamic ethics mediate the effect of service quality on decision quality, and whether these pathways differ by gender. Responses from 153 accountants were analyzed using PLS-SEM with permutation-based multi-group analysis. Service quality showed no direct effect on decision quality but a strong total effect, transmitted entirely through accountant behaviour and Islamic ethics, consistent with full mediation, with the behavioural channel carrying somewhat more of the transmission than the ethical one. Two of five paths differed by gender. Investments in service quality translate into better decisions only when accountants enact them through professional conduct and ethical commitment.